Analisis Kimia Dan Mikrobiologi Bumbu Rujak Gula Merah Dalam Kemasan Yang Dijual Di Denpasar - Komang Nita Wedaningsih; Ni Made Ayu Suardani Singapurwa; I Gede Pasek Mangku (GEMA AGRO, 2021)
Brown sugar salad is a type of snack or snack that is popular with the public because it is cheap and rich in vitamins. This study aims to identify the chemical and microbiological contents of the packaged brown sugar rujak spices sold in Denpasar. This research is a descriptive study using survey and experimental methods in the laboratory. The number of samples to be studied is 31 samples. The parameters in the study were analysis of sodium benzoate preservative, analysis of artificial sweeteners saccharin, moisture content, degree of acidity (pH), total plate count (TPC), analysis of Escherichia coli contaminants and organoleptic tests. The results showed that of the 31 samples the results of testing for the preservative sodium benzoate were all negative. The test results for the artificial sweetener Saccharin showed that 4 samples were positive for saccharin. The water content of the rujak spices ranged from 13.97% -71.91%. While the pH value obtained ranges from 3.54-5.76. The results of the Total Pate Count (TPC) test showed that 31 samples of rujak spices had total microbes ranging from <10 - 9.1x107 colonies / g. A total of 6 samples of rujak spices had total microbes that exceed 1 x 105 colonies / g. Escherichia coli test results showed that all rujak spices had a total of E. coli <3.6 colonies / g. Organoleptic test results as a whole rujak spices accepted by consumers.